2021
DOI: 10.1101/2021.04.14.21255512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the Mortality Impact of the COVID-19 Pandemic in Florida State Prisons

Abstract: Background The increased risk of COVID-19 infection among incarcerated individuals due to environmental hazards is well known and recent studies have highlighted the higher rates of infection and mortality prisoners in the United States face due to COVID-19. However, the impact of COVID-19 on all-cause mortality rates in incarcerated populations has not been studied. Methods Using data reported by the Florida Department of Corrections on prison populations and mortality events we conducted a retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Finally, all of the included studies stated that the risk of COVID-19 infection in prisons was higher than in the general population, thus, prevention measures were needed to reduce the risk of transmission. In fact, Marquez, N.M. et al [ 31 ] calculated a mortality in 2020 that was 42% higher than that of 2019, of which 80.4% was due to COVID-19. Jiménez, M.C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, all of the included studies stated that the risk of COVID-19 infection in prisons was higher than in the general population, thus, prevention measures were needed to reduce the risk of transmission. In fact, Marquez, N.M. et al [ 31 ] calculated a mortality in 2020 that was 42% higher than that of 2019, of which 80.4% was due to COVID-19. Jiménez, M.C.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] tested some Canadian prisoners through swabs by PCR analysis for SARS-CoV-2 and found 29% positives compared with 6% of the general population (non-prisoners); mortality was 0.6%. Marquez et al [ 31 ], on the other hand, through a retrospective cohort study using data reported by the Florida Department of Corrections, stated that, comparing mortality in prisons from 2015 to 2019 with that of 2020, mortality in 2020 was 42% higher, with 80.4% deaths related to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only are incarcerated people more vulnerable to COVID-19 (3,4), but COVID-19 policies in prisons may have exacerbated risk of death from other causes (2,15,16). Therefore, all-cause mortality rates among incarcerated people likely increased during the pandemic, as a result of both COVID-19 infection and pandemicrelated changes that transformed the confinement experiences of incarcerated people.…”
Section: Introductionmentioning
confidence: 99%
“…Second, prisons faced unprecedented constraints on their staff and their medical resources, limiting access to routine primary and specialty medical care and delaying the timely delivery of care (20), exacerbating the risk of deaths due to natural causes, including but not limited to COVID-19. Third, prisons imposed policies attempting to mitigate infection-such as lockdowns and restricted movements, programming suspensions, visitor prohibitions, limited communication with loved ones, and solitary confinement in lieu of medical isolation-all of which increased stress, mental health challenges, and violence (2,15,16,20,21,22,23), exacerbating the risk of deaths due to unnatural causes, such as drug overdoses, suicide, and violence.…”
Section: Introductionmentioning
confidence: 99%